Religion against Domination: The Politics of William James's Individualism - Bush, Stephen S. (Journal of the American Academy of Religion, 2015)
After a long period of neglect, William James's political philosophy has been receiving significant attention in the past two decades. For the most part, however, those interested in his political thought do not attend to his philosophy of religion and vice versa. In this article, I argue that we can understand the individualism that James famously promotes in Varieties of Religious Experience as very much a political ideal. The sort of religious individuality that James endorses does not abjure social responsibility but rather involves an activist commitment to improve religious and societal institutions.